Uwarunkowania szacunkowego ustalenia podstawy opodatkowania - Pasieczna, Ewa (The Conditions of Tax Base Estimation Setting, 2006)
Tax inspection verifies taxpayers' tax self-calculation on the basis of the tax declaration submitted by them. During such a control the inspection has the right to evaluate the correctness of a taxpayer's activity in the matter of his establishing of all factors of the actual condition that directly affect the amount of his tax liabilities and the way of application of legal regulation in force in the time an event occurred. Tax institutions, however, often encounter the situations when reconstructing the events creating the tax liability is difficult or sometimes impossible. It happens, for example, when a taxpayer undertakes the actions aiming at minimizing tax charges. In such situations on the basis of art. 23 of tax regulations one may use the tax base estimated setting in order to reconstruct the course of commercial events and their influence on the amount of tax liability. The article describes the circumstances in which a tax institution may effectively apply the institution of estimated setting of tax base.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 322-328